(untitled) (Research, Society and Development, 2021)
This article proposes a brief theoretical review on the use of active methodologies in professional and technological education. To do so, it was necessary to reflect on professional education in integrated high school education and how the Common National Curriculum Base influences this context. Based on this reflection, the work also analyzes the use of active methodologies and information and communication technologies applied in the area, as well as the training of teachers in the use of these resources. Thus, the discussions raised during theorization made it possible to understand that it is necessary to break with the duality of student (digital native) and teacher (digital foreigner) if what is aimed at is a pedagogical proposal that minimally approximates the generational differences between both. Thus, it is necessary to wake up to the multiplicity of issues involving the use of these new methodologies and technologies, as in-depth discussions on their inclusion in pedagogical projects, training paths and teacher training are still incipient. It is hoped that this bibliographic survey can conduct to a qualified discussion or infusion of a protagonist, active and reflective education within the scope of professional education.